Feminist perspectives on tort law - Richardson, Janice; Rackley, Erika (Milton Park, Abingdon, Oxon : Routledge, 2012)
Feminist Perspectives on Tort Law offers a distinctly feminist approach to key topics in tort law. Ten original essays written by feminist legal scholars from the UK, US, Canada and Australia encompass a range of ways of thinking about women, tort law and feminism. The collection provides a fresh and original analysis of issues of long-standing concern to feminists as well as nascent areas of concern. These include conceptions of harm, constructions of reasonableness, the duty of care, the public/private divide, sexual wrongdoing, privacy and environmental law. Written with both.
Includes bibliographical references and index.
Keywords: Torts -- England; Torts -- Wales; Torts; Women -- Legal status, laws, etc. -- England; Women -- Legal status, laws, etc. -- Wales